2014
DOI: 10.22158/wjssr.v1n2p136
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Visual Pathologies among Nursing Home Residents: An Evaluation of Light Conditions and Recording in Client Files

Abstract: Objective: Reflection on visual problems in nursing homes. Data Sources: Eye examinations, documented visual problems and illuminance levels. Principal findings: 50% of the referred residents had problems with cataracts, retinal problems (21%), suspected glaucoma (13%), and other pathologies (16%). The information was not current in 56% of the records. The quality of lighting conditions was low or moderate. Conclusion: The finding of poor lighting conditions in nursing homes in combination with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Despite this, the results of this study fit with earlier field studies in Dutch nursing homes showing low awareness of care professionals on visual functioning (Sinoo et al, 2012;Sinoo et al, 2014).…”
Section: Study Limitationssupporting
confidence: 87%
See 2 more Smart Citations
“…Despite this, the results of this study fit with earlier field studies in Dutch nursing homes showing low awareness of care professionals on visual functioning (Sinoo et al, 2012;Sinoo et al, 2014).…”
Section: Study Limitationssupporting
confidence: 87%
“…Earlier studies have shown that eye problems are often insufficiently recorded in client files (Sinoo et al, 2014;Owsley et al, 2007) and that light conditions in many nursing homes are of poor quality (Aarts et al, 2014;Hegde & Rhodes, 2010;Aarts & Westerlaken, 2005) and often below the recommended threshold for visual function in older adults (750 -1000 lux) (Hegde & Rhodes, 2010;Aarts & Westerlaken, 2005;Sinoo et al, 2011). Therefore, this study aimed to examine both the role of NHPs in eye care and in this respect also the relationship between NHPs and other involved professionals, by using a survey from the NHPs perspective.…”
Section: Eye Diseases and Visual Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,[12][13][14] The importance of awareness of nursing home residents' visual functioning has been addressed by former studies. [6,[13][14][15][16] A supporting tool might raise professional caregivers' awareness of these environmental factors, indicated as (building) physical aspects in Figure 1. In a pilot study, [17] the content and layout of the Environmental Observation tool for the Visually Impaired (EOVI-63) was determined by use of a literature search and open observations in seven nursing homes.The tool was developed because previous studies howed that nursing homes had poor light conditions and because of professional caregivers' lack of awareness of these light conditions and their effect on the residents.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study, [17] the content and layout of the Environmental Observation tool for the Visually Impaired (EOVI-63) was determined by use of a literature search and open observations in seven nursing homes.The tool was developed because previous studies howed that nursing homes had poor light conditions and because of professional caregivers' lack of awareness of these light conditions and their effect on the residents. [15,16] The tool targets indoor light related aspects of the nursing home environment, such as quality of light, the use of colours & contrasts and furnishing & obstacles, to prevent residents from falling. These aspects concern items in common rooms, corridors and bathrooms in nursing homes.…”
Section: Introductionmentioning
confidence: 99%